-8x-(3x+6)=4-1x

Simple and best practice solution for -8x-(3x+6)=4-1x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x-(3x+6)=4-1x equation:


Simplifying
-8x + -1(3x + 6) = 4 + -1x

Reorder the terms:
-8x + -1(6 + 3x) = 4 + -1x
-8x + (6 * -1 + 3x * -1) = 4 + -1x
-8x + (-6 + -3x) = 4 + -1x

Reorder the terms:
-6 + -8x + -3x = 4 + -1x

Combine like terms: -8x + -3x = -11x
-6 + -11x = 4 + -1x

Solving
-6 + -11x = 4 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-6 + -11x + x = 4 + -1x + x

Combine like terms: -11x + x = -10x
-6 + -10x = 4 + -1x + x

Combine like terms: -1x + x = 0
-6 + -10x = 4 + 0
-6 + -10x = 4

Add '6' to each side of the equation.
-6 + 6 + -10x = 4 + 6

Combine like terms: -6 + 6 = 0
0 + -10x = 4 + 6
-10x = 4 + 6

Combine like terms: 4 + 6 = 10
-10x = 10

Divide each side by '-10'.
x = -1

Simplifying
x = -1

See similar equations:

| 5x-4=1-x | | (y^2-4y+3)/(5y^2-40y+35) | | 4y-3(2y-7)=5y+12 | | v^2-v=30 | | x-5+3x/4=-5+7x/4 | | x+2-8=14 | | 28+a+(-48.08)*(1.414213562)=0 | | 2t+3=-12 | | 34+a+(-48.08)*(1.414213562)=0 | | 5(-3b+2)=40 | | 34+a+(-48.08)*1.414213562=0 | | 10+9(x-2)=13x-4(x+4) | | 10k+13r=(276)(12) | | 10a+120=8 | | -(2x-8)+1=7x+9(1-x) | | 95-7x=20x+17 | | y=2x^2-20x+45 | | 7x-14(x+1)=-7x+23 | | 5x-25=30-4x+5-3x | | 1/3-x+1/8=x/3 | | (-2x^2)(3x^2y)(-y)= | | 2+0.1(27-x)=1.5x-(0.5x-2.5) | | 81-3x=8x+16 | | 7x=-8 | | 6x-1=2x(x-1) | | 8x-18=5x-3 | | x*2+11x+28=0 | | 1/2(x+6)+1/3(x-4)=3/4 | | 128*13/12*1/16 | | x^3-x=5 | | x+3/4=15x+2 | | 9x+10=3x-4 |

Equations solver categories